PERANCANGAN DAN EVALUASI UNJUK-KERJA REPEAT-ACCUMULATE CODESUNTUK KANAL KOMUNIKASI NIRKABEL DENGAN RELE - , Daryus Chandra ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wireless communication system has developed very rapidly because it offers high flexibility. However, wireless communication systems suffer a phenomenon that is difficult to overcome called multipath fading . One of the methods offered to reduce the effect of multipath fading is a wireless communication systems with relay . Various communication protocols with relay and coding schemes have been introduced to overcome these problems. In this research decode-and-forward protocol is used and RAC coding scheme is chosen for relay channel. RAC is chosen because it has a simple structure, has low complexity encoding scheme, and supported by iterative decoding. The results showed that the use of relays in LOS channel resulting performance improvements compared to a wireless communication system without relay if the relay is positioned right in the middle between the information source and destination. While in urban areas the channel model, the relay communication system showed performance improvements whether the relay is positioned ½, ¼ , or ¾ from the information source. Optimal position is achieved if the relay is positioned right in the middle between the information source and destination.